2022
DOI: 10.1002/1438-390x.12118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and origin of a fish population recently colonizing a reservoir: The case ofBasilichthys microlepidotus, central Chile

Abstract: Freshwater ecosystems are among those most affected by human activity. Constructing artificial reservoirs can change freshwater biodiversity, thereby impacting genetic diversity (GD), which is crucial to population-level adaptation. The Maipo River basin, inhabited by the endemic silverside Basilichthys microlepidotus, is one of Chile's most impacted freshwater systems. In this basin, the species is divided into five populations. Recently, a new population was discovered in the reservoir Laguna Esmeralda (LE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…The site designated as MEL showed the most remarkable results in terms of diversity indices, possibly due to the considerable influx of immigrants, mainly from the PEL and SFM sites. Previous studies of the same populations using microsatellite markers have consistently shown a similar trend: a relatively low rate of self-recruitment in the MEL population, which is the lowest of all populations, with immigration coming mainly from the PEL and SFM populations 22 , 23 . It is noteworthy that, despite the considerable migration from PEL and from SFM in MEL, no recognisable genetic homogeneity could be detected.…”
Section: Discussionsupporting
confidence: 62%
“…The site designated as MEL showed the most remarkable results in terms of diversity indices, possibly due to the considerable influx of immigrants, mainly from the PEL and SFM sites. Previous studies of the same populations using microsatellite markers have consistently shown a similar trend: a relatively low rate of self-recruitment in the MEL population, which is the lowest of all populations, with immigration coming mainly from the PEL and SFM populations 22 , 23 . It is noteworthy that, despite the considerable migration from PEL and from SFM in MEL, no recognisable genetic homogeneity could be detected.…”
Section: Discussionsupporting
confidence: 62%